Digital breast tomosynthesis. - Baldwin P (Radiologic Technology)
Digital breast tomosynthesis (DBT) is a new technology that combines the use of tomography and 3-D reconstruction with breast imaging to improve lesion visibility. Although no DBT equipment yet has been approved by the U.S. Food and Drug Administration, the technology is creating interest in the United States and research on its effectiveness continues around the world. This Directed Reading describes the current state of tomosynthesis technology and addresses the challenges faced by DBT researchers and manufacturers, as well as the potential challenges facing the radiologists and technologists who will use DBT in the future.